Breakfast Skipping and Determinant Factors among Moroccan School Adolescents (12-19 Years): The Case of Beni Mellal City - Kamal Kaoutar; Ahmed Chetoui; kaltoum Boutahar; Soufiane El Moussaoui; Abdeslam El Kardoudi; Mohamed Najimi; Fatiha Chigr (Karger Publishers, 2023)
Introduction: Breakfast skipping is an unhealthy eating behavior reportedly common among adolescents. The aim of the present study was to determine the prevalence and factors associated with breakfast skipping among schoolchildren aged 12-19 years in Beni Mellal city, Morocco, and to assist in the design of interventions to improve breakfast consumption habits of school-aged children in this region. Methods: A school-based cross-sectional study was carried out. A total of 550 children were included in the study. Multivariable logistic regression analysis was used to identify factors associated with skipping breakfast consumption. The association between dependent and independent variables was assessed using an odds ratio (OR) with a 95% confidence interval and p value <0.05 was considered statistically significant. Results: Among 550 Moroccan adolescents evaluated, 25.6% reported not consuming breakfast every day. Breakfast eating was statistically associated with gender (OR = 7.13 [95% CI 1.32-3.84], p = 0.008); mother's low educational level (OR = 2.86 [95% CI 1.89-4.71], p = 0.091); nonworking mothers (OR = 13.71 [95% CI 1.16-5.29], p < 0.001); not eating between meals (OR = 15.49 [95% CI 2.15-5.49], p < 0.001); eating dinner regularly each day (OR = 17.79 [95% CI 2.81-8.01], p = 0.005); eating vegetables 1-3 times per week (OR = 10.21 [95% CI 1.44-4.67], p = 0.001); consuming milk and dairy product 1-3 times per week (OR = 13.88 [95% CI 1.59-5.56], p < 0.001); and never consuming sodas and soft drink in week (OR = 3.12 [95% CI 1.90-4.50], p = 0.003). Conclusions: This study revealed that the prevalence of skipping breakfast consumption among school-aged children in Beni Mellal city was high. Thus, the findings suggest a community health education program, conducted by school nurses, nutritionists, and other health professionals, is needed.